Processes of change in the field of corporate sustainability and the contributions of tha holders of capital : a case study in a company in the textile sector - Pires, Amélia Maria Martins (2023)
Factors with a negative impact on the environment, such as the excessive use of natural resources or global warming, are the basis for adopting more sustainable and environmentally friendly measures. A process of change that does not allow anyone to be left out, neither people nor companies, and that has gained relevance as the latter have come to realize that adopting the path of sustainability could translate into added value. The textile sector,from which reports of efforts in this direction come to us, is an example of this, so, within the scope of an analysis and reflection around the main concepts of sustainability, we will seek to understand the role and contributions of the holders of capital for sustainability. This study explores the role of capital holders in promoting sustainability in business through an exploratory case study conducted at Sourcetextile, a company operating in the textile sector. The results found indicate that Sourcetextile presents a sustainable behavior, based on the three pillars of sustainability, and that this is due to the social and environmental concerns of entrepreneurs, which creates a kind of permanent tension between economic and environmental objectives. and social, without which the company would only be concerned with economic objectives.